Proses Corporate Rebranding Framework oleh PT. Telekomunikasi Seluler Indonsesia - Kurniawan, Agnikafitriya; Hafiar, Hanny; Sani, Anwar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
In the digital era, Telkomsel is trying to commit and continue to adapt by carrying out corporate rebranding, which aims to change the company's brand image, which is quite old in the public eye. Through the descriptive research method, the researcher wants to analyze the